NCAPG Is a Promising Therapeutic Target Across Different Tumor Types - Xiao, Cuicui; Gong, Jiao; Jie, Yusheng; Cao, Jing; Chen, Zhongcheng; Li, Rong; Chong, Yutian; Hu, Bo; Zhang, Qi (Frontiers in Pharmacology, 2020)
Abstract Background: With CRISPR-Cas9 genome editing tool in gene therapy, identifying aberrantly expressed genes is of great value across various cancer types. A large number of patients may benefit from molecular targeted gene therapy. The purpose of this study was to identify aberrantly expressed genes across various cancer type, analyze prospective mechanism and theirs correlation with survival outcomes. Results NCAPG was highly expressed in The Cancer Genome Atlas (TCGA) database, which includes the transcriptomes of 6647 cancer and 647 normal tissue samples from 16 cancer types. Furthermore, a predicted NCAPG overexpression rate was also observed at the protein level in 16 tumor types. Importantly, high NCAPG level was significantly associated with unfavorable survival not only in HCC, breast, lung or ovarian cancer with TCGA database but also in HCC with an extra Gene Expression Omnibus Datasets (GEO) dataset. The multivariate analyses demonstrated that NCAPG, TNM and Barcelona Clinic Liver Cancer staging were independent risk factors for mortality of patients with HCC. Moreover, functional and pathway enrichment analysis suggested that NCAPG was overrepresented in the pathways of cell cycle, cellular senescence, mismatch repair and p53 signaling pathway. By weighted gene co-expression network analysis (WGCNA), we identified NCAPG as a hub gene in the turquoise module mostly related to the survival time of HCC samples. Conclusion To our knowledge, this study represents the first comprehensive RNA-Seq analysis of several types of tumor revealing NCAPG as a promising molecular target and NCAPG overexpression may play important roles in carcinogenesis and progression of tumors through regulating tumor-related pathways, thereby broadening the understanding of the pathogenic mechanisms and highlighting the possibility of developing novel targeted therapeutics.